DEVELOPING THE ORGANIZATIONAL MANAGEMENT SYSTEM OF IMPROVING THE QUALITY OF HOUSEHOLD SERVICES - Erejepova Bibisara Abibullaevna (Scholar Express Journals, 2024)
In this article, the quality management system in household service enterprises, the specific nature of household service to the population, the quality control of household service to the population, the development of corporate standards for the provision of household service, the main goals of the policy of household service service quality, the organizational management of the quality of household service elements of the system were studied.
Keywords: Household service industry; quality management system